2011
DOI: 10.3389/fnins.2010.00207
|View full text |Cite
|
Sign up to set email alerts
|

Type 7 Adenylyl Cyclase is Involved in the Ethanol and CRF Sensitivity of GABAergic Synapses in Mouse Central Amygdala

Abstract: The GABAergic system in the central amygdala (CeA) plays a major role in ethanol dependence and in the anxiogenic response to ethanol withdrawal. Previously, we found that both ethanol and corticotropin releasing factor (CRF) increase GABAergic transmission in mouse and rat CeA neurons, in part by enhancing the release of GABA via activation of presynaptic CRF1 receptors. CRF1 receptors are coupled to the enzyme adenylyl cyclase (AC), which produces the second messenger cyclic AMP. There are nine isoforms of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…However, because we have previously shown that application of 44 mM ethanol always augments PPF in outbred rodents (Bajo et al, 2008; Cruz et al, 2011; Roberto et al, 2003; Roberto et al, 2004a; Roberto et al, 2004b), we tested whether the lack of ethanol effect on PPF in CD 14 KO CeA might result from the inclusion of higher doses, which do not generate PPF. When the effects of 44 mM ethanol were analyzed separately by two-way repeated measures ANOVA, we found a significant ethanol application × mouse strain interaction (F(1,17) = 5.6; p < 0.05) with no main effects of mouse strain or ethanol application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because we have previously shown that application of 44 mM ethanol always augments PPF in outbred rodents (Bajo et al, 2008; Cruz et al, 2011; Roberto et al, 2003; Roberto et al, 2004a; Roberto et al, 2004b), we tested whether the lack of ethanol effect on PPF in CD 14 KO CeA might result from the inclusion of higher doses, which do not generate PPF. When the effects of 44 mM ethanol were analyzed separately by two-way repeated measures ANOVA, we found a significant ethanol application × mouse strain interaction (F(1,17) = 5.6; p < 0.05) with no main effects of mouse strain or ethanol application.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these findings indicate that both TLR4 and the GABAergic system, and their cellular interactions in the CeA, may play an important role in ethanol drinking. However, little is known about the cellular aspects of TLR4 activation on neurophysiology and GABAergic transmission or on ethanol-induced potentiation of GABAergic transmission in the CeA (Bajo et al, 2008; Cruz et al, 2011; Roberto et al, 2012; Roberto et al, 2003; Roberto et al, 2004b). Therefore, in the present study we explored these issues using electrophysiological methods in CeA slices from CD14 KO mice, with exogenous administration of LPS and the TLR4 antagonist (+)-naloxone to activate and inhibit TLR4, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the adenylate cyclase pathway is one of the second messenger pathways engaged by ethanol and CRF receptor activation (Cruz et al, 2011;Cruz et al, 2012). We speculate that the adenylate cyclase pathway may represent a common signaling pathway targeted in the same directions by ghrelin and ethanol in regulating GABAergic transmission, thus playing an essential role in their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism(s) for alcohol effects have yet to be identified, we showed that activation of adenylyl cylase (AC) and/or protein kinase C (PKC) mediate GABAergic transmission in CeA synapses (Bajo et al 2008;Cruz et al 2011). In CeA slices of mice lacking PKC1 or pretreated with a PKC1 antagonist, the ability of acute alcohol to augment IPSCs is impaired (Bajo et al 2008), suggesting that PKC1 facilitates alcohol-elicited vesicular GABA release.…”
Section: Acute Alcohol Augments Gabaergic Transmission In Ceamentioning
confidence: 98%